(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2011)
A field experiment was conducted comprising eighteen advanced lines of mustard in a randomized block design with three replication at Regional Agricultural Research Station, BARI, Hathazari, Chittagong during Rabi season (December 2009 to April 2010) for estimation of divergence among advanced lines of mustard. The genotypes were grouped into four clusters. Cluster I contained the highest number of genotypes (6) and the cluster III contained the lowest (3). The inter-cluster distances in all cases were larger than the intra-cluster distance which indicated that wider diversity was present among the genotypes of distant grouped. The highest intra cluster distance was observed in cluster II and the lowest in I. The highest inter cluster distance was observed between the cluster III and II followed by III and I and the lowest between cluster IV and III. Days to 50% flowering (81.94%), days to maturity (8.24%), plant height (5.82%), branches per plant (1.91%) and siliquae per plant (1.17%) contributed maximum towards the total divergence which suggested that these characters were highly responsible for genetic divergence in the present materials. But the highest cluster means for primary branches per plant and maximum seeds per siliquae with minimum seed yield per plant were obtained from the cluster II. The genotypes from cluster I had dwarf plant along with earliness in days to 50% flowering, days to maturity and maximum number of primary branches per plant. Therefore, the genotypes from cluster I and III could be utilized in the hybridization programme for getting desirable transgressive segregants and high heterotic response due to getting maximum yield along with short duration. Key words: Multivariate analysis; Divergence; Mustard DOI: http://dx.doi.org/10.3329/bjpbg.v23i2.9322 Bangladesh J. Pl. Breed. Genet., 23(2): 29-34, 2010